2009
DOI: 10.1088/0022-3727/42/8/085309
|View full text |Cite
|
Sign up to set email alerts
|

Energy spike effects in ion-bombarded GaN

Abstract: We study structural disorder in GaN bombarded at room temperature with 1.3 keV amu−1 PFn (n = 0, 2 and 4) cluster ions. Results are compared with our previous studies of irradiation with atomic ions of different masses. An algorithm for cascade density calculations that take into account the formation of subcascades is presented. Quantitative analysis of both new and previous data shows that an increase in the cascade density above a certain critical value results in a rapid increase in the rate of planar amor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
22
0
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 33 publications
(77 reference statements)
8
22
0
3
Order By: Relevance
“…The cascade density effect during ion irradiation was studied by maintaining the following parameter constant: ion energy normalized to ion mass, ion dose normalized to the number of displacements per atom (DPA) and ion beam flux normalized to DPAs −1 [14,85]. Here, DPA= Φ× g v /n at , where Φ is ion dose, g v is the SRIM [86] calculated number of ion-beam-generated lattice vacancies at the maximum of the nuclear energy loss profile, and n at is the atomic density of the target.…”
Section: Ion Irradiation Of Ganmentioning
confidence: 99%
See 3 more Smart Citations
“…The cascade density effect during ion irradiation was studied by maintaining the following parameter constant: ion energy normalized to ion mass, ion dose normalized to the number of displacements per atom (DPA) and ion beam flux normalized to DPAs −1 [14,85]. Here, DPA= Φ× g v /n at , where Φ is ion dose, g v is the SRIM [86] calculated number of ion-beam-generated lattice vacancies at the maximum of the nuclear energy loss profile, and n at is the atomic density of the target.…”
Section: Ion Irradiation Of Ganmentioning
confidence: 99%
“…This is explained by the overlap of separate cascades composing the cluster of fluorine and phosphorus atoms in a narrow near-surface region to a depth of ∼10-12 nm. between the efficiency of damage buildup and the density of collision cascades where cluster ions produce denser cascades than single ions [14]. In the following, damage production in GaN by single and molecular ion irradiation has been studied by means of atomistic simulation based on the above contexts.…”
Section: Ion Irradiation Of Ganmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous experiments for different materials have revealed that the efficiency of the formation of stable damage generally increases with increasing m 6891013161718193132. However, even the qualitative behavior is non-trivial and depends strongly on the material and irradiation conditions such as Φ, F , and T .…”
Section: Resultsmentioning
confidence: 98%